Splenic Infarction in Plasmodium Falciparum Malaria: Case Report and Review of Literature - Dwivedi, Deepak; Singh, Jyoti (Journal of Nepal Paediatric Society, 2016)
Splenic involvement is frequently observed during malarial episode. This involvement may vary from simple asymptomatic splenic enlargement to serious complication such as hematoma, rupture, or infarction. Very few cases of splenic infarction in paediatric patients are reported in literature. This case report suggests that if a patient with malaria is complaining of left upper quadrant abdominal pain, and/or enlarging tender splenomegaly is observed during treatment, splenic infarct should be suspected and managed accordingly to avoid further life-threatening complications. J Nepal Paediatr Soc 2015;35(3):298-300